The stubborn porridge and other stories - Wang, Meng 1934- (Braziller, 1994)
In the title story, one of eight, a family adapts to the modern world. Its first lifestyle change: replacing the time-honored menu of pickles and porridge with a Western-style breakfast.
Aus d. Chines. übers.
Keywords: Wang, Meng <1934-> -- Translations into English; Alltag, Brauchtum; China -- Social life and customs -- Fiction